Effects of additional weight-bearing on the in vivo kinematics of the human ankle joint complex during walking - Shengli Wang; Zhihui Qian; Xiangyu Liu; Guangsheng Song; Zhende Jiang; Kunyang Wang; Jianan Wu; Jing Liu; Lei Ren; Luquan Ren (Scientific Reports)
Abstract Studies focusing on the kinematics of the ankle joint complex (AJC) have long been a key area of interest for biomechanists and orthopedic surgeons. However, it is not clear how additional weight-bearing walking affects the motion of the AJC compared to walking with a normal body weight (BW) or what adjustments the AJC would instinctively make to accommodate the additional load. To address this gap in knowledge, advanced dynamic biplane radiography combined with a model-based 2D-3D tracking technique was employed to elucidate the inherent kinematics of the AJC during the stance phase while walking with and without additional weight-bearing. It was found that walking with additional 50% body weight (BW + 50%) resulted in a greater dispersion of instantaneous axes of rotation in the talocrural and subtalar joints during the stance phase of gait. The talocrural joint is more plantarflexed and anteriorly translated during the early and late stance phases than during the midstance phases, which suggests that additional weight-bearing affects the stability of the AJC. Moreover, walking with BW + 50% showed that the center of rotation of the talocrural joint was positioned more superiorly and posteriorly during the foot flat to heel-off phase. This, accordingly, increases the ankle-foot gear ratio and the force of the dorsiflexors.